2023
DOI: 10.3390/min13111376
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Materials Based on Clay and Soapstone Waste: Thermo-Mechanical Properties and Application

Vera Ilyina,
Ekaterina Klimovskaya,
Tatiana Bubnova

Abstract: In order to assess the feasibility of utilizing soapstone waste, which is generated during the production of stone blocks for fireplaces and other energy-saving devices, the effect of its addition to clay on the technological and thermal properties of ceramic materials was investigated. Two local clays and soapstone processing waste were characterized using XRD, SEM-EDS, XRF, DTA-TG, and granulometric analysis. The linear firing shrinkage, water absorption, density, flexural strength, thermal conductivity, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The most important raw materials in tile production are clays with a controlled purity grade. The purity grade is related to the prevalence of kaolinite and possibly muscovite particles in the clay, which often are found as small fractions [6,7]. Some research regarding clay particles has indicated that kaolinite has nanostructured fractions [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The most important raw materials in tile production are clays with a controlled purity grade. The purity grade is related to the prevalence of kaolinite and possibly muscovite particles in the clay, which often are found as small fractions [6,7]. Some research regarding clay particles has indicated that kaolinite has nanostructured fractions [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…When kaolinite particles are under intensive movement, admixture with other, harder, mineral particles like quartz might act as milling bodies generating very small fractions. Such a mechanism was observed in the quartz-kaolinite interaction in environmental street dust [11,12], but it is currently used in raw material preparation in the ceramic industry for porcelain pottery [13,14] and ceramic tiles [15,16]. The mineral admixture is milled under a wet condition at a very well-controlled humidity level to obtain ceramic paste, which is further molded into dies.…”
Section: Introductionmentioning
confidence: 99%